Morally Wrong Beauty as a Source of Value - Alcaraz León, María José (The Nordic Journal of Aesthetics, 2011)
<!–StartFragment–> In this paper I would like to address the problem of the aesthetic value of damaged nature. A variety of arguments have been offered in order to ground the view that we cannot perceive damaged nature as beautiful, at least as soon as we are aware of its damaged condition. These arguments are usually offered in tandem with a view about what the correct appreciation of nature involves and, hence, are often supported by this view. I will try to show that none of these arguments are compelling and that there seems to be a way of explaining how damaged nature can be beautiful without disposing of the intuition that the awareness of its damaged condition penetrates our perception. <!–EndFragment–>